‘I eat to kill hunger’: the foods of Cape Verde and the double-edged sword of globalisation - Lam, K. (Shima, 2020)
Cape Verde is a former Portuguese colony that experienced devastating droughts and famines with dire demographic and social consequences up to the last century. As the popular saying goes, “Cabo Verde não é verde” : ie Cape Verde (meaning ‘Green Cape’) is the opposite of what its name suggests. The islanders treasure food because they know how their ancestors and older family members suffered, maintaining to this day a close and grateful relationship with the land. Insular as it is, this archipelago is not immune to globalisation. This study examines some changes in the Cape Verdean diet induced by globalisation, the way food is produced and distributed, and how locals perceive and adapt to these trends. It draws preponderantly on five sessions of fieldwork on five of the nine inhabited islands undertaken between 2016 to 2019. It suggests that globalisation contributes to new urban dynamics and may have homogenising and demoralising effects on rural food traditions but also facilitates a range of synthetic experiences between these tendencies.